2000
DOI: 10.4049/jimmunol.164.8.4089
|View full text |Cite
|
Sign up to set email alerts
|

Independent Functioning of Cytosolic Phospholipase A2 and Phospholipase D1 in Trp-Lys-Tyr-Met-Val-D-Met-Induced Superoxide Generation in Human Monocytes

Abstract: Recently, a novel peptide (Trp-Lys-Tyr-Met-Val-D-Met, WKYMVm) has been shown to induce superoxide generation in human monocytes. The peptide stimulated phospholipase A2 (PLA2) activity in a concentration- and time-dependent manner. Superoxide generation as well as arachidonic acid (AA) release evoked by treatment with WKYMVm could be almost completely blocked by pretreatment of the cells with cytosolic PLA2 (cPLA2)-specific inhibitors. The involvement of cPLA2 in the peptide-induced AA release was further supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…Some viral chemokine homologues bind to chemokine or chemoattractant receptors, alter receptor activation properties, and inhibit the proper functioning of receptor-mediated immune responses (47). Because HIV T-20 peptide and H. pylori Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peptide are ligands of FPR and FPRL2, respectively, it appears that these pathogen-derived agonists suppress DC-mediated immune responses by activating FPR or FPRL2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viral chemokine homologues bind to chemokine or chemoattractant receptors, alter receptor activation properties, and inhibit the proper functioning of receptor-mediated immune responses (47). Because HIV T-20 peptide and H. pylori Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) peptide are ligands of FPR and FPRL2, respectively, it appears that these pathogen-derived agonists suppress DC-mediated immune responses by activating FPR or FPRL2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that WKYMVm induces human monocytes and neutrophils to generate cellular superoxide and to undergo chemotactic migration (11)(12)(13). Three cell surface G-protein-coupled WKYMVm receptors have been identified (14 -16), namely, formyl peptide receptor (FPR), FPR-like 1 (FPRL1), and FPR-like 2 (FPRL2) (14 -16).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…This correlates with the ligand binding analysis that showed the existence of multiple receptors for WKYMVm in the DC2.4 cells. (Milella et al, 1999;Bae et al, 2000;Melendez et al, 2001). Examination of WKYMVM effect on the PLD activation in the DC2.4 cells was carried out by using transphosphatidylation, a characteristic reaction of PLD in the presence of 0.5% normal butanol (n-butanol).…”
Section: Dc24 Cells Express Fpr1 and Fpr2mentioning
confidence: 99%
“…fMet-Leu-Phe (fMLP), a prototypic bacterium-derived chemotactic agonist, was shown to induce the translocation of ARF-regulated PLD activity to the plasma membrane in human neutrophils [23]. It was reported recently that fresh circulating human monocytes express detectable levels of PLD1 protein [24].…”
Section: Introductionmentioning
confidence: 99%